2010
DOI: 10.1074/jbc.m110.160606
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Pharmacophore Influences Active Site Specificity of Proteasome Inhibitors

Abstract: Proteasomes degrade most proteins in mammalian cells and are established targets of anti-cancer drugs. The majority of proteasome inhibitors are composed of short peptides with an electrophilic functionality (pharmacophore) at the C terminus. All eukaryotic proteasomes have three types of active sites as follows: chymotrypsin-like, trypsin-like, and caspase-like. It is widely believed that active site specificity of inhibitors is determined primarily by the peptide sequence and not the pharmacophore. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 29 publications
(41 reference statements)
3
56
0
2
Order By: Relevance
“…This finding is also in agreement with their superior binding strength over MG132, which features an IC 50 value of 270 nM against the ChTL activity in vitro. Although it has been shown that inhibition of β5 alone is sufficient for cytotoxicity of a compound, it is considerably increased if also a second subunit is affected (27). This furthermore explains the enhanced effects of the syrbactin compounds, which bind both to the β5 and the β2 subunits.…”
Section: Resultsmentioning
confidence: 87%
“…This finding is also in agreement with their superior binding strength over MG132, which features an IC 50 value of 270 nM against the ChTL activity in vitro. Although it has been shown that inhibition of β5 alone is sufficient for cytotoxicity of a compound, it is considerably increased if also a second subunit is affected (27). This furthermore explains the enhanced effects of the syrbactin compounds, which bind both to the β5 and the β2 subunits.…”
Section: Resultsmentioning
confidence: 87%
“…Targeting the CT-L active site has long been considered as sufficient to develop new candidate drugs for cancer treatment; yet, inhibition of multiple active sites is usually required to decrease markedly protein degradation and produce more relevant biological effects [5]. So, beyond the β5 active site, it is also important to target either the β1 or β2 active sites, considered as co-targets of cancer drugs [6,7,8]. Specific assays were developed to monitor independently the three individual catalytic activities of the proteasome and a number of selective inhibitors were identified [9,10,11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…6) have a preference for hydrophobic and aromatic residues in most positions, consistent with the chymotrypsin-like activity of this subunit. Both VS and EK warheads have been evaluated, with EKs typically showing greater reactivity but reduced selectivity over b1 and b2 subunits [39,44]. Modification in the P1 and P3 positions can confer selectivity for either the b5c or b5i subunit: b5c favors a small hydrophobic group in P1 and a large hydrophobic group in P3, while b5i favors the reverse arrangement [35,40,45].…”
Section: Subunit-selective Abpsmentioning
confidence: 99%